Bedroom layout based on Feng Shui conception for sleep quality improvement: Case study of young female adults in Malaysia / Hong Wan Thing - Hong , Wan Thing (2018)
Feng Shui practices in a sleep environment have been criticised as myth over the years but in fact having its scientific origin that is not purely superstitious. This research intended to investigate whether the recommended Feng Shui approaches in bed arrangement is supportive to greater sleep efficiency and subsequently develop a design protocol for bedroom interior, specifically to young female adults in Malaysia. The research was conducted using a mixed methods triangulation approach. A self-report survey questionnaire was carried out to provide the human majority preferences in bed arrangement. Interviews to professional (interior) architects were also conducted to seek for their perceptions for the most ideal bedroom layout to boost sleep efficiency. Both survey and interviews were analysed using quantitative method. To reduce the validity problems in perception studies, case study by sleep experiments were then carried out using actigraphy monitoring system. The study delivered three findings in stages. Firstly, the most preferable bedroom arrangement was found to be identical to Form School Feng Shui model; and concurrently in compliance with the recommended bedroom Feng Shui rules in all situations. Secondly, the architect’s perceptions of an ideal bedroom layout were predominantly determined as conforming to the recommended bedroom Feng Shui rules. Lastly, the bed arrangements according to favourable Feng Shui rules were validated as supportive to greater sleep efficiency among young female adults throughout the nights of experiments. Consequently, a design protocol for bedroom interior arrangement was developed based on the three research findings. The overall findings supported that Feng Shui approaches in bed arrangement are scientific knowledge. It is expected to be valued as a contribution in sleep study and sleep environmental research, and as a foundation for future research in bedroom Feng Shui.